﻿Les écrits de Wassily Kandinsky ou le discours des fondements de la peinture abstraite - Doyon, Carol (RACAR : Revue d'art canadienne / Canadian Art Review, 1990)
Wassily Kandinsky is considered today one of the most prestigious abstract painters of the twentieth century. Despite his important role as the founder of vanguard movements such as Die Neue Künstlervereinigung, Der Blaue Reiter, etc. and as the theoretician of modern art through his numerous writings, his main achievement is more often than not centred on the “inventio” of abstraction. A certain art history likes to introduce him as the necessary link in the accomplishment — the “telos” — of modernism which would be highly visible within the stylistic transformations of his works, especially as one looks at them retrospectively. Within this System, it works as if artists never question the pertinence of their art and were oblivious to the status of their own production in art history: they are naturally considered as “prophets of their times” while not in the least concerned with the games of fame and the struggle for power.It seems that the three main texts of Kandinsky — Concerning the Spiritual in Art, The Blue Rider Almanach, and Reminiscences — written between 1911 and 1914 are not only interesting in regard to the avant-garde movements of the period and the explanations they provide for Kandinsky’s novel painting, but mainly because they are the means of an extraordinary “mise en scène” by the artist himself. A rhetorical analysis of these texts brings into light the construction of Kandinsky’s artistic identity and historical necessity which is still in effect today and on which modernist painting finds its legitimacy.